1994
DOI: 10.1111/j.1468-232x.1994.tb00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Productivity Gains from the Implementation of Employee Training Programs

Abstract: This study uses data on the personnel policies and economic characteristics of businesses in the manufacturing sector to measure the impact of formal training programs on labor productivity. The major finding is that businesses that were operating below their expected labor productivity levels in 1983 implemented new employee training programs after 1983 that resulted in significantly larger increases in labor productivity growth between 1983 and 1986. This higher rate of productivity growth was sufficient to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
268
1
45

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(321 citation statements)
references
References 3 publications
7
268
1
45
Order By: Relevance
“…It is found by Katz, Kochan, and Gobeille (1983) and Schuster (1983) that labor-management teams, quality circles, and quality of work life (QWL) improved productivity. A relationship between the implementation of training plans and productivity augmentation is found by Bartel (1994) and Holzer (1987) illustrated that widespread efforts intended for recruiting improved productivity. It is expressed by Guzzo, Jette, and Katzell's (1985) that socio technical system design, goal setting, and training had considerable and positive impacts over productivity.…”
Section: Organizational Performancementioning
confidence: 99%
“…It is found by Katz, Kochan, and Gobeille (1983) and Schuster (1983) that labor-management teams, quality circles, and quality of work life (QWL) improved productivity. A relationship between the implementation of training plans and productivity augmentation is found by Bartel (1994) and Holzer (1987) illustrated that widespread efforts intended for recruiting improved productivity. It is expressed by Guzzo, Jette, and Katzell's (1985) that socio technical system design, goal setting, and training had considerable and positive impacts over productivity.…”
Section: Organizational Performancementioning
confidence: 99%
“…Bartel found that some businesses implemented new employee training programs in 1983 and they received significantly larger increases in labour productivity growth from 1983 to 1986 [8]. Storey and Westhead found that the take-up of management training in small firms is lower than large firms [9].…”
Section: Educational Trainings For the Randd Institutions: State Of Thementioning
confidence: 99%
“…Bartel (1994) and Batt (1999) found that employee productivity, service quality and customer satisfaction increased the more training employees received. Curtis et al (2012) found that employee training was associated with profitability.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the advantages and importance of training for job and organizational performance have been extensively documented and researchers have found positive associations between training and several job factors (Aguinis & Kraiger, 2009;Bartel, 1994;Batt, 1999;Curtis et al, 2012). Bartel (1994) and Batt (1999) found that employee productivity, service quality and customer satisfaction increased the more training employees received.…”
Section: Introductionmentioning
confidence: 99%